2013
DOI: 10.1007/s11356-013-2392-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and particle size on the thermal desorption of PCBs from contaminated soil

Abstract: Thermal desorption is widely used for remediation of soil contaminated with volatiles, such as solvents and distillates. In this study, a soil contaminated with semivolatile polychlorinated biphenyls (PCBs) was sampled at an interim storage point for waste PCB transformers and heated to temperatures from 300 to 600 °C in a flow of nitrogen to investigate the effect of temperature and particle size on thermal desorption. Two size fractions were tested: coarse soil of 420-841 μm and fine soil with particles <250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Since the treatments of co-contaminated soils are limited, it is widely agreed that multiple costly techniques are required (Khan et al 2004). A number of investigations have shown that thermal treatment (thermal desorption, incineration, pyrolysis, gasification, and vitrification) is one of the effective processes for complex substances remediation (González-Corrochano et al 2012;Qi et al 2014;Qin et al 2015;Taube et al 2008;Van Caneghem et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since the treatments of co-contaminated soils are limited, it is widely agreed that multiple costly techniques are required (Khan et al 2004). A number of investigations have shown that thermal treatment (thermal desorption, incineration, pyrolysis, gasification, and vitrification) is one of the effective processes for complex substances remediation (González-Corrochano et al 2012;Qi et al 2014;Qin et al 2015;Taube et al 2008;Van Caneghem et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another method is to add alkali metal carbonates, which will react and lead to pyrolysis [ 108 ]. Highly effective is thermal desorption for removing PCBs from soils [ 109 ]. Microbial degradation of soils is possible by adding Shewanella oneidensis to contaminated soils [ 110 ].…”
Section: Methods Of Pcb Destruction—limiting Exposurementioning
confidence: 99%
“…Bulmau et al [19] studied the effect of heating temperature on soils polluted by polycyclic aromatic hydrocarbons (PAHs) and indicated that the removal efficiency increased from 5% at 350 • C to 80% at 650 • C when processed for the same time. Qi et al [20] found that the removal efficiencies after heating at 600 • C for 20 min, 40 min and 60 min are 20.86%, 64.47% and 95.7% respectively. The removal rate for polychlorinated biphenyls (PCBs) within the 20-40 min interval is greater than that of the first 20 min.…”
Section: Introductionmentioning
confidence: 99%